Electrochemical characterization of the marine antioxidant gadusol - Arbeloa, Ernesto Maximiliano (2012)
The electrochemical properties of gadusol, a metabolite extracted from fish roes, were determined for the first time by cyclic- and square-wave voltammetries on a glassy carbon electrode in buffered aqueous solutions. The aims of the work were characterization of the redox behavior and assessment of the mechanism underlying the antioxidant capacity of the compound. Anodic waves with peak potentials of 710 ± 5 mV and 601 ± 9 mV vs. Ag/AgCl were obtained for gadusol and its anion gadusolate, respectively. The voltammograms point to the irreversible nature of the oxidation process and reveal better antioxidant properties for the compound under physiological pH, with a moderate reductive power, but improved stability under atmospheric oxidation in comparison with other natural antioxidants such as ascorbic acid. The presence of direct ionic micelles prepared with sodium dodecyl-sulfate or cetyl-trimethyl-ammonium chloride yielded no significant differences regarding homogeneous medium in the cyclic voltammetry of gadusolate. The results provide evidence of the electron transfer mechanism for the quenching reaction of standard-reactive species by gadusolate and support it as a promising candidate to be tested as an antioxidant additive to food, cosmetic and pharmaceutical formulas. The direct analysis of the metabolite in biological systems and natural extracts by electrochemical methods is also envisaged.